2016
DOI: 10.1108/jamr-10-2015-0072
|View full text |Cite
|
Sign up to set email alerts
|

Agreement-seeking behavior, trust, and cognitive diversity in strategic decision making teams

Abstract: Purpose The purpose of this paper is to investigate the effect of three important group process variables, namely, agreement-seeking behavior, group trust, and cognitive diversity, on decision outcomes. In addition, it seeks to examine the role of process conflict as a moderator in the relationship between agreement-seeking behavior and team effectiveness; agreement-seeking behavior and decision commitment; cognitive diversity and team effectiveness; and cognitive diversity and decision commitment. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
2
13
0
1
Order By: Relevance
“…Regarding the impact of cognitive diversity on performance ; it has been shown that cognitive diversity in work group can contribute to many positive outcomes, such as minimizing debiasing decision making (Meissner & Wulf, 2017) and improving decision quality (Parayitam & Papenhausen, 2016). An experimental research verified that decision errors decrease as the number of cognitive styles increase (West & Dellana, 2009).which in turn, enhance creative formulations of responses ( Hambrick, Cho, & Chen, 1996).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the impact of cognitive diversity on performance ; it has been shown that cognitive diversity in work group can contribute to many positive outcomes, such as minimizing debiasing decision making (Meissner & Wulf, 2017) and improving decision quality (Parayitam & Papenhausen, 2016). An experimental research verified that decision errors decrease as the number of cognitive styles increase (West & Dellana, 2009).which in turn, enhance creative formulations of responses ( Hambrick, Cho, & Chen, 1996).…”
mentioning
confidence: 99%
“…since heterogeneity in terms of both idea generators (Innovators) and idea codifiers and organizers (Adapters) important for creativity ( Kurtzberg, 2005). Through the creativity process, members will have the benefit of getting a variety of information, thoughts and ideas because of the diversity in the functional backgrounds and educational backgrounds of other team members (Parayitam & Papenhausen, 2016). Other scholars agreed that homogeneity is preferred for team performance; they describe the role of group cohesion for enhancing coordination and thus team outcomes (King & Anderson, 1990).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…vista (Jehn, 2008;Loughry & Amason, 2014). Nas equipes de direção, esse tipo de conflito é comumente considerado benéfico por levar os codirigentes a considerar diferentes contribuições, perspectivas e possibilidades de solução na tomada de decisões (Weingart et al, 2015;Parayitam et al, 2016;Hjerto et al, 2017). Dado o considerável potencial benéfico do conflito cognitivo na tomada de decisão, faz-se promissor e atraente investigá-lo com vistas a esclarecer sua ocorrência e consequências, particularmente na decisão estratégica de PE (Behfar, Mannix, Peterson & Trochim, 2010;Todorova, Bear & Weingart, 2014;Tjosvold, Wong & Feng Chen, 2014;Weingart et al, 2015).…”
unclassified